The relationship between ID and the cutting time, where SD means without damage, PD means partial damage, and ED means extreme damage. - Abdallah Elshawadfy Elwakeel (19852263) (2024)
The relationship between ID and the cutting time, where SD means without damage, PD means partial damage, and ED means extreme damage.